New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes